Experimental investigation on the mechanical properties and pore structure deterioration of fiber-reinforced concrete in different freeze-thaw media. (3rd October 2022) - Lu, Jianguo; Liu, Junni; Yang, Huohai; Wan, Xusheng; Gao, Jiajia; Zhang, Jiacheng; Li, Pengcheng
Highlights: The mechanical properties and pore structure deterioration of FRCs in five freeze-thaw media (i.e. WF, NF, SSF, SCF, HSF) were studied. The influence of the SCF on the mechanical properties of FRCs is the greatest, followed by the HSF, SSF, WF and NF. There is an optimal fiber dosage for the FRCs to resist freeze-thaw cycle and salt erosion. The porosities and salt corrosion degree of the FRCs exposed on the freeze-thaw cycles significantly increased. Abstract: More engineering infrastructures have been built in cold regions and even permafrost area with salt-rich media, such as seawater, saline soil or groundwater. In such environment, the concrete is not only destroyed by freeze-thaw processes, but also damaged by corrosion. Therefore, this study investigated the mechanical properties and pore structure deterioration of fiber-reinforced concrete (FRC) in five types freeze-thaw media, i.e., water (WF), natural air (NF), 5 % sodium sulfate solution (SSF), 5 % sodium chloride solution (SCF), a mixture of the 5 % sodium sulfate and 5 % sodium chloride solution (HSF). A total of 180 freeze-thaw cycles were carried out on steel fiber-reinforced concrete (SFRC), polypropylene fiber-reinforced concrete (PPFRC), and basalt fiber-reinforced concrete (BFRC). The compressive strength and elastic modulus of FRCs after freeze-thaw cycles were measured to observe the influence of different media and fibers on the mechanical properties. The deterioration of the pore structure of the FRCs was observed by SEM (scanning electron microscope), XRD (X-ray diffraction), and MIP (mercury intrusion porosimetry) tests. The results show that the influence of the SCF on the mechanical properties of concrete is the greatest, followed by HSF, SSF, WF and NF. Moreover, there is an optimal fiber dosage for the FRCs to resist freeze-thaw cycles and salt erosion, the optimal fiber dosages for the SFRC, PPFRC and BFRC were 2 %, 2 ‰ and 0.5 ‰, respectively. Additionally, compared to the concrete not exposed to freeze-thaw cycles in the NF, the porosities of the FRCs exposed to the freeze-thaw cycles significantly increased. Under the same freeze-thaw media, the porosity of the BFRC is larger than that of the PPFRC. Furthermore, for the FRCs in the SSF, the proportions of gel micro-pores (<10 nm) decreased with the number of freeze-thaw cycles, whereas the proportions of capillary pores (10–5000 nm) and macro-pores (>5000 nm) increased.